2018
DOI: 10.1089/cyber.2017.0708
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Side of Social Comparison on Social Network Sites: How Envy Can Drive Inspiration on Instagram

Abstract: A growing body of research finds social network sites (SNS) such as Instagram to facilitate social comparison and the emotional experience of envy in everyday life, with harmful effects for users' well-being. Yet, previous research has exclusively focused on the negative side of social comparison and envy on SNS. Thereby, it has neglected two important aspects: (a) comparison processes can also elicit a beneficial emotional reaction to other users' online self-presentations (i.e., benign envy) and, thus, (b) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(142 citation statements)
references
References 36 publications
7
128
1
6
Order By: Relevance
“…(3) The branded application level refers to variables that focus only on one or several branded application(s), such as Facebook or Instagram. While these branded platforms can be subsumed under broader types of applications (e.g., SNS), they are frequently studied individually as key exemplars (e.g., Meier & Schäfer, 2018). It is important to distinguish this level of analysis from the previous one, as unique applications may have properties and cultures that diverge from other applications or their broader types.…”
Section: Six Levels Of Cmc Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…(3) The branded application level refers to variables that focus only on one or several branded application(s), such as Facebook or Instagram. While these branded platforms can be subsumed under broader types of applications (e.g., SNS), they are frequently studied individually as key exemplars (e.g., Meier & Schäfer, 2018). It is important to distinguish this level of analysis from the previous one, as unique applications may have properties and cultures that diverge from other applications or their broader types.…”
Section: Six Levels Of Cmc Analysismentioning
confidence: 99%
“…However, both approaches have their pitfalls. Technology-centered measures of exposure, especially selfreports, are notoriously unreliable (e.g., Orben, 2020) finding "upward comparison on Instagram" negatively affects well-being cannot inform upon whether this is an effect of upward comparison, characteristics of Instagram, or both (e.g., Meier & Schäfer, 2018). Our recommendation for future research is therefore a combination of the technology-and user-centered approaches: Studies should strive to measure technology use descriptively, ideally via digital tracking (e.g., Bayer, Ellison, Schoenebeck, Brady, & Falk, 2018) and at multiple levels of the taxonomy, to allow comparisons.…”
Section: Measuring Cmc and Social Media Usementioning
confidence: 99%
See 1 more Smart Citation
“…Among these sites, Instagram (IG) is a photo-and video-sharing platform where users can follow stories, publish or comment on posts, watch or upload content, and chat privately. Some evidence demonstrated that increased Instagram activity may be associated with positive [6] and negative [7] outcomes. However, environmental influence is insufficient in explaining a tangled phenomenon like social behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…User behavior ini mempelajari pola berpikir dan pola berinteraksi antara satu orang dengan lainnya di dalam media sosial. Diharapkan dengan mempelajari user behavior dapat menentukan strategi apa yang dibutuhkan oleh para pelaku bisnis UMKM (Waluyo & Budiarsi, 2018 (Meier & Schäfer, 2018).…”
Section: Pengantarunclassified